Investigating the Indian ethnic groups of Afghan descent - Mohammad Israfeel Azadzoi; Mullajan Rahmani; Sayed Habibullah Radmanish (Science and Education, 2024)
A number of small ethnic minorities of Afghanistan of Indian origin, who have resided in this geography throughout different periods of history and live in a limited and scattered way in different parts of the country, these small ethnic minorities include Sikhs and Hindus, jets, Prachis, Gujaras, Brahvians, etc. Is. These small ethnic minorities of the country, which in the past, due to various factors of lack of a specific border between countries, the occurrence of various historical events and currents, the conquests of rulers and emperors, the increase of population and the lack of specific occupation in The Geography of India, the warm climate of that geography, have led to the dragging of these small ethnic, linguistic and cultural minorities to the geography of Afghanistan that live in urban and rural areas of the country. And it has maintained the independence of the country. The aim of this study was to introduce the number of small ethnic minorities of the country of Indian origin. The importance of this study is that by these researches, it is found how many ethnic and linguistic minorities live in this country and which factors have caused their dispersion. The research method of this issue was in the form of libraries and the Internet, which resulted in the acquisition of information and awareness about ethnic, linguistic and religious minorities of those of Indian origin.